A new chromene flavanone from Dalea boliviana Britton (Fabaceae) against Candida tropicalis biofilms - Lombardo, Andrea Laura (2020)
Currently, a wide variety of natural products are used for medicinal purposes, both to prevent and treat health problems, as well as in the research and development of new drugs. Previous studies on the species Dalea elegans Gillies ex Hook. et Arn, led to the isolation and elucidation of a prenylated flavonoid: 2’,4’-dihydroxy-5’-(1’’’,1’’’-dimethylallyl)-8 prenylpinocembrin (8PP). This compound exhibited antimicrobial activity against bacterial and fungal strains and was also reported with activity against Candida albicans mature biofilms. This species is the most frequently isolated from candidiasis, however, the incidence of fungal infections produced by C. non-albicans has increased in recent years in Latin America. Antifungal treatment can be difficult, often associated with the ability to form a biofilm, with high resistance to antifungal agents. This work aimed to perform the chemical study and evaluations of the antibiofilm activity of the species D. boliviana Britton (Fabaceae) as a potential source of new structures for the investigation of antifungal drugs. The chemical study of D. boliviana was performed by obtaining the hexane extract from its roots. This extract was purified by column chromatography and thin-laye chromatography. A solid, amorphous, and orange-colored compound (N3) was isolated and purified. N3 structure was determined by spectroscopic methodologies (NMR H1 and C13 in one and two dimensions) and UV-Vis spectrophotometry. N3 activity was evaluated in vitro on mature biofilms of C. tropicalis (NCPF 1111). The mature biofilm was treated with N3 dissolved in dimethyl sulfoxide (2% DMSO), at a final concentration of 25 µg/mL, with Amphotericin B (AmB) at 100 µg/mL, and with the combination of both. The results were reported as relative percentages of inhibition with respect to the control (mature biofilms without treatment). As a result of the analysis of the spectral data, the new structure named 5,2’-dihydroxy-6’’,6’’-dimethylchromeno-(7,8:2’’,3’’)-flavanone (N3), is postulated. It is a chromeno flavanone reported for the first time in the species D. boliviana. Compound N3 by itself reduced 54 ± 4% of the mature biofilm of C. tropicalis, while Amb reduced 86 ± 2%. For the combination of both compounds, the inhibition resulted in 98 ± 3%. In conclusion, this work presents a new compound obtained from the Argentine native flora showing activity against a highly resistant structure such as the mature biofilm of C. tropicalis. Furthermore, when the compound N3 was combined with AmB, the total eradication of the biofilm was obtained. Since Candida biofilms have marked resistance to antifungals for clinical use, it is important to obtain new active compounds against this form of growth, so it would merit the continuity of this research, especially in the search for synergistic combinations and studies on the mechanism of action.